Primary Cutaneous Cryptococcosis Treated with Debridement and Fluconazole Monotherapy in an Immunosuppressed Patient: A Case Report and Review of the Literature - Jennifer Wang; Luther Bartelt; Deborah Yu; Anjali Joshi; Bradley Weinbaum; Tiffany Pierson; Michael Patrizio; Cirle A. Warren; Molly A. Hughes; Gerald Donowitz (Case Reports in Infectious Diseases)
Cryptococcus neoformans is an opportunistic yeast present in the environment. Practitioners are familiar with the presentation and management of the most common manifestation of cryptococcal infection, meningoencephalitis, in patients with AIDS or other conditions of immunocompromise. There is less awareness, however, of uncommon presentations where experience rather than evidence guides therapy. We report a case of primary cutaneous cryptococcosis (PCC) in a patient who had been immunosuppressed by chronic high-dose corticosteroid for the treatment of severe asthma. This case highlights the importance of early recognition of aggressive cellulitis that fails standard empiric antibiotic treatment in an immunocompromised patient. It also demonstrates successful treatment of PCC with a multispecialty approach including local debridement and fluconazole monotherapy.